Escola, gênero e masculinidades – é possível fazer uma escola que debata as diferenças? - Santos, Janiê Lidia Maia Cunha (2022)
Studies on masculinities still do not constitute a large number of articles and debate groups on the subject, although we witnessed the emergence of great researchers in the late 1980s on the subject, we observed that the mistake persists of relating Gender Studies only as studies of gender. women, given that gender is a relational concept; and this mistake generates research in a single sphere of the genre. This research goes beyond the traditional sphere of gender and seeks to analyze, conceptualize and relate about masculinities, specifically how masculinities are debated at school. The objective of this work is a sociological attempt to understand the symbolic, cultural and institutional mechanisms of analyzing masculine perceptions in society and how they are perpetuated in the school environment. The research methodology was the questionnaires applied by the students of the school institution EEEP MARLY FERREIRA MARTINS for each professionalizing course offered by that institution, the literary sources on the imaginary and history of masculinity, scientific articles, student testimonials and information derived from the observations in the school. This research is structured in three parts: the first part is about a brief genesis on gender; the second part presents the school, gender and masculinities – the locus of research; the third part is led by interventions and results. This study resulted in a product to be used in Sociology classes - a lesson plan produced for high school Sociology teachers - respecting the characteristics of Sociology teaching, such as denaturalization, debate and the sociological perspective. From this result, we can conclude that it is more than necessary for studies on men (masculinities) to be structured within the school, through textbooks, classroom debate, BNCC and the political pedagogical project of each school system